Darwinism, democracy, and race : American anthropology and evolutionary biology in the twentieth century - Jackson, John P., 1961-; Depew, David J., 1942- (London : Routledge, 2017)
"Darwinism, Democracy, and Race examines the development and defence of an argument that arose at the boundary between anthropology and evolutionary biology in twentieth-century America. In its fully articulated form, this argument simultaneously discredited scientific racism and defended free human agency in Darwinian terms. The volume is timely because it gives readers a key to assessing contemporary debates about the biology of race. By working across disciplinary lines, the book';s focal figures--the anthropologist Franz Boas, the cultural anthropologist Alfred Kroeber, the geneticist Theodosius Dobzhansky, and the physical anthropologist Sherwood Washburn--found increasingly persuasive ways of cutting between genetic determinist and social constructionist views of race by grounding Boas';s racially egalitarian, culturally relativistic, and democratically pluralistic ethic in a distinctive version of the genetic theory of natural selection. Collaborators in making and defending this argument included Ashley Montagu, Stephen Jay Gould, and Richard Lewontin.Darwinism, Democracy, and Race will appeal to advanced undergraduates, graduate students, and academics interested in subjects including Philosophy, Critical Race Theory, Sociology of Race, History of Biology and Anthropology, and Rhetoric of Science."--Provided by publisher.
chapter 1 Introduction: in the footsteps of Franz Boas -- chapter 2 Franz Boas and the argument from presumption -- chapter 3 Demarcating anthropology: the boundary work of Alfred / Kroeber -- chapter 4 Theodosius Dobzhansky and the argument from definition -- chapter 5 Unifying science by creating community: the epideictic rhetoric of Sherwood Washburn -- chapter 6 A kairos moment unmet and met: the controversy over Carleton Coon$1 (Bs The Origin of Races -- s chapter 7 Epilogue: the roots of the Sociobiology controversy, the infirmities of Evolutionary Psychology, and the unity of anthropology.
Keywords: Anthropology; Evolution (Biology)